A Theory of Disappointment Aversion - Gul, Faruk (Econometrica, 1991)
An axiomatic model of preferences over lotteries is developed. It is shown that this model is consistent with the Allais paradox, includes expected utility theory as a special case, and is only one parameter (" beta") richer than the expected utility model. Allais paradox type behavior is identified with positive values of "beta." Preferences with positive "beta" are said to be disappointment averse. It is shown that risk aversion implies disappointment aversion and that the Arrow-Pratt measures of risk aversion can be generalized in a straight-forward manner to the current framework. Copyright 1991 by The Econometric Society.